Physical activity as a factor influencing mental health: integrating neurobiological mechanisms, regulatory processes, and the sports context - Kurek, Maria Michalina; Polit-Różycka, Oliwia Kinga; Baltyzar, Konstancja Anna; Gadzalski, Krzysztof; Rogowski, Filip Robert; Chrabąszcz, Joanna; Grzywna, Wojciech; Lorek, Julia; Perski, Karol; Zarzycka, Marta (Quality in Sport, 2026)
Physical activity (PA) is a recognized protective factor for mental health; however, its mechanisms of action and the variability of its therapeutic effects remain the subject of active research. This paper is a narrative review of the literature aimed at synthesizing available data on the neurobiological and behavioral mechanisms of PA, along with an analysis of environmental factors that modulate its effectiveness, with a particular focus on the context of competitive sports. Physical activity influences mental health through three main mechanisms: neuroplasticity based on the stimulation of neurotrophic factors, the regulation of metabolic and inflammatory processes, and the improvement of executive function and cognitive control. These effects are simultaneously significantly modulated by systemic factors, such as sleep quality, the severity of psychosocial stress, and the interpersonal environment. Based on our analysis, we identify three trajectories of response to physical activity and propose a three-level integrative model encompassing biological, psychological, and environmental dimensions. An analysis of competitive sports as a boundary model reveals the limitations of a simplified understanding of the relationship between the amount of physical activity and mental well-being and highlights the need to consider contextual factors when designing therapeutic interventions.